The Effect of Visual Media Education in the Management Therapy on the Level of Knowledge of Patients Diabetes Mellitus with Comorbid - Utami, Primanitha Ria; Devi Ristian Octavia (JURNAL INFO KESEHATAN, 2023)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both and is often accompanied by increased blood pressure. One of the drug-related problems that are frequently encountered is patient non-compliance in taking drugs. This can occur due to a lack of knowledge about managing pharmacological and non-pharmacological therapies, making therapeutic outcomes difficult. This study aims to determine the effect of visual media education on managing pharmacological and non-pharmacological treatment on the level of knowledge of type 2 DM patients with comorbid hypertension. This type of research is quasi-experimental, with pretest and posttest designs without a control group design. The research sample is the age group that has the age of 18-68 years, as many as 123 people using Purposive Sampling. The results showed that the level of knowledge before being given education was in a good category (4.81%), sufficient (42.29%), and less (52.90%). After being given education visual media, there was an increase in knowledge results for the good (74.25%), sufficient (18.14%) and poor (7.61%) categories. The results of the Wilcoxon test analysis obtained a p-value (0.000) < (0.005), which means that there is an effect of visual media education on the level of knowledge of type 2 DM patients with comorbid hypertension. Through the results of this study, it is hoped that pharmacists can provide ongoing educational counselling to chronic disease patients receiving polypharmacy to prevent drug-related problems.